An Empirical Study on the Asymmetric Behavior of Scientometric Indicator for Journal: A Comparative Evaluation of SJR and H-Index - Kalita, Deepjyoti; Sai Baba, M.; Deka, Dipen (Journal of Information and Knowledge, 2018)
Scimago Journal Rank (SJR) is a size independent measure of journal evaluation where citation coming from quality journals carries more value than citations from ordinary journals and h-index, used as a metrics for author impact when initially introduced, is now a day’s used for journal evaluation in major citation databases like Scopus, Google scholar etc. Both the indicators follow different methods of calculation. SJR is a prestige based measure where the scholarly value of incoming citations matters most than its quantity, while h-index is a quantity based measure where the amount of incoming citations plus the number of published paper both matters. The current study tries to identify how the ranking value of journals changes when compared with the two indicators. The issue was addressed by taking the context of Indian journals indexed in Scopus. Even though the process of calculation for both the indicators is different, it is expected that their ultimate result is same i.e. ranking quality journals at top. The findings of ranking of quality journals represent strikingly different result given by both the indices. The dissimilarity in measure is tested using z-test for two sample means for median difference. Also the biasness of the indicators towards time and subject domains is tested on a raw count.